Factors Affecting Electrocoagulation Process for Different Water Types: A review - Abed AL-Rubaye, Shahad Fadhil; A. AlHaboubi, Naseer; Al-Allaq, Aiman H. (Al-Khwarizmi Engineering Journal, 2024)
Raw water must meet specific physical, chemical, and biological requirements to be suitable for drinking. There are various techniques available for treating wastewater, and aside from conventional methods that involve chemicals, electrocoagulation is an efficient and advanced approach. Electrocoagulation has proven effective in treating many pollutants, including bacteria, viruses, iron, fluoride, sulfate, boron, hardness, and turbidity. Total suspended solids, organic and inorganic materials, chemical oxygen demand COD, biochemical oxygen demand BOD, and color. It finds extensive application in treating different types of water and wastewater due to its exceptional ability to remove diverse contaminants. Recently, electrocoagulation has garnered significant attention due to its remarkable efficiency in treating various pollutants. This article provides a thorough analysis of contemporary literature that is committed to using electrocoagulation in a variety of water treatment methods, with a focus on the different variables affecting the process performance, such as electrical current, electrode type, electrode configuration, initial pH, electrode distance, NaCl concentration, initial concentration of pollutants, operating temperature and electrolysis time.